Knowledge and training in paediatric medical traumatic stress and trauma-informed care among emergency medical professionals in low- and middle-income countries. Issue 1 (1st January 2018) - Hoysted, Claire; Babl, Franz E.; Kassam-Adams, Nancy; Landolt, Markus A.; Jobson, Laura; Van Der Westhuizen, Claire; Curtis, Sarah; Kharbanda, Anupam B.; Lyttle, Mark D.; Parri, Niccolò; Stanley, Rachel; Alisic, Eva
ABSTRACT: Background : Provision of psychosocial care, in particular trauma-informed care, in the immediate aftermath of paediatric injury is a recommended strategy to minimize the risk of paediatric medical traumatic stress. Objective : To examine the knowledge of paediatric medical traumatic stress and perspectives on providing trauma-informed care among emergency staff working in low- and middle-income countries (LMICs). Method : Training status, knowledge of paediatric medical traumatic stress, attitudes towards incorporating psychosocial care and barriers experienced were assessed using an online self-report questionnaire. Respondents included 320 emergency staff from 58 LMICs. Data analyses included descriptive statistics, t -tests and multiple regression. Results : Participating emergency staff working in LMICs had a low level of knowledge of paediatric medical traumatic stress. Ninety-one percent of respondents had not received any training or education in paediatric medical traumatic stress, or trauma-informed care for injured children, while 94% of respondents indicated they wanted training in this area. Conclusions : There appears to be a need for training and education of emergency staff in LMICs regarding paediatric medical traumatic stress and trauma-informed care, in particular among staff working in comparatively lower income countries.